Improvement of beef cattle through breeding. - Smith, W.H.; Holland, L.A.; Wheat, J. (Kansas Agricultural Experiment Station, 2011)
The purebred Shorthorn cattle breeding project, established to study the production traits and the effects of inbreeding, was continued during the last year. Two inbred lines were established by the use of the two herd sires, College Premier 29th 2368167 and Gregg Farm's Hoarfrost 2492499. The two breeding groups are referred to as the Wernacre Premier and the Mercury lines, respectively, in reference to the foundation sires. The Wernacre Premier line has entered the third generation of inbreeding and the Mercury line is as yet in the first generation of inbreeding.
Keywords: Beef; Breeding; Inbreeding; Rations